The Synaptic Theory of Memory: A Historical Survey and Reconciliation of Recent Opposition - Langille, Jesse J.; Brown, Richard E. (Frontiers in Systems Neuroscience, 2018)
Trettenbrein (2016, Frontiers in Systems Neuroscience, 10:88) has argued that the concept of the synapse as the locus of memory is outdated and has made six critiques of this concept. In this paper we examine these six critiques and suggest that the current theories of the neurobiology of memory and the empirical data indicate that synaptic activation is the first step in a chain of cellular and biochemical events that lead to memories formed in cell assemblies and neural networks that rely on synaptic modification for their formation. These neural networks and their modified synaptic connections can account for the cognitive basis of learning and memory and for memory deterioration in neurological disorders. We first discuss Hebb's (1949) theory that synaptic change and the formation of cell assemblies and phase sequences can link neurophysiology to cognitive processes. We then examine each of Trettenbrein's (2016) critiques of the synaptic theory in light of Hebb's theories and recent empirical data. We examine the subcellular basis of memory formation and the necessity of synaptic modification to form the neural networks underlying learning and memory. We then provide evidence for the value of Hebb's theories of synaptic change and cell assemblies for integrating neurophysiological and cognitive conceptions of learning and memory. We examine some of the critiques of Hebbian theories and conclude with an examination of the applications of the Hebb synapse and cell assembly theories to the study of the neuroscience of learning and memory, the development of computational models of memory and the construction of ‘intelligent’ robots. We conclude that the synaptic theory of memory has not died but come to dominate our understanding of the neural basis of memory.